Revisiting the renin-angiotensin-aldosterone system in the eye: Mechanistic insights and pharmacological targets - Francesco Buonfiglio; Elsa Wilma Böhm; Qi Tang; Andreas Daiber; Adrian Gericke (Pharmacological Research)
The renin-angiotensin-aldosterone system (RAAS) plays a fundamental role in regulating blood pressure and fluid homeostasis through key effectors such as angiotensin II and aldosterone. These agents and their receptors have become crucial molecular targets in several cardiovascular and renal diseases. Over the past few decades, a growing body of evidence has revealed the presence of RAAS components in ocular structures, suggesting a tissue-specific RAAS within the eye. Building on this knowledge, studies have indicated that the ocular RAAS plays a significant role in the pathogenesis of various eye diseases. An impaired and overactivated RAAS contributes to the development of severe and widespread disorders affecting both the anterior and posterior segments of the eye. In this context, the current work aims to delve into the pivotal molecular pathways involving the RAAS, with an in-depth exploration of the ocular pathophysiology. It focuses on the relationship between overactivation of the RAAS and oxidative stress, as well as the exacerbation of neovascularization and inflammatory processes. The objective is to provide an updated and comprehensive understanding of the role of the RAAS in ophthalmological diseases, highlighting the therapeutic potential of RAAS modulators and discussing the controversies and challenges in this area of research.